1995
DOI: 10.1099/00207713-45-2-301
|View full text |Cite
|
Sign up to set email alerts
|

Haloanaerobium alcaliphilum sp. nov., an Anaerobic Moderate Halophile from the Sediments of Great Salt Lake, Utah

Abstract: A strictly anaerobic, moderately halophilic, gram-negative, rod-shaped bacterium was isolated from Great Salt Lake, Utah, sediments and designated GSLST (T = type strain). Strain GSLST grew optimally at pH 6.7 to 7.0 but had a very broad pH range for growth (pH 5.8 to 10.0). The optimum temperature for growth was 37"C, and no growth occurred at 15 or 55°C. The optimum salt concentration for growth was 10%. Strain GSLST required yeast extract and Trypticase peptone to ferment carbohydrates, pyruvate, and glycin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…In hypersaline environments, betaine is a common osmoregulatory compound synthesized at high concentrations by certain halophilic bacteria (42). Betaine can be fermented to yield acetate and trimethylamine by a variety of fermentative bacteria, including halophilic acetogens and other halophiles (19,37,53). Specifically, it has been demonstrated that a methanogen fermenter coculture of Methanohalophilus sp.…”
Section: Discussionmentioning
confidence: 99%
“…In hypersaline environments, betaine is a common osmoregulatory compound synthesized at high concentrations by certain halophilic bacteria (42). Betaine can be fermented to yield acetate and trimethylamine by a variety of fermentative bacteria, including halophilic acetogens and other halophiles (19,37,53). Specifically, it has been demonstrated that a methanogen fermenter coculture of Methanohalophilus sp.…”
Section: Discussionmentioning
confidence: 99%
“…praevalens, H. saccharolyticum and H. congolense. In addition, the maximum pH for growth for strains VS-751T, VS-5 11 and VS-732 is 8.0 while H. alcaliphilurn, H. praevalens and H. congolense can grow at pH values greater than 8.0 (Ravot et al, 1997;Zeikus et al, 1983;Tsai et al, 1995). The growth of H. lacusroseus was inhibited by magnesium chloride while the three strains examined here tolerated at least 1 M magnesium chloride.…”
Section: Cellular Fatty Acid Compositionmentioning
confidence: 83%
“…salsugo (Bhupathiraju et al, 1994a) was phenotypically the most similar to strains VS-751T, VS-51 l and VS-732. H. salsugo produced more acetate than ethanol from glucose (Bhupathiraju et al, 1994a) et al (1994aet al ( ), Cayol et al (1994, Ravot et al (1997), Rainey et al (1995), Rengpipat et al (1988), Tourova et al (1995, Tsai et al (1995), Zeikus et al (1983) and Zhilina et al (1992 The phenotypic variability among strains VS-75 lT, VS-511 and VS-732 seems unusual since all three strains were isolated from the same hypersaline oil reservoir, which also contained another phenotypically similar species of Haloanaerobium (Bhupathiraju et al, 1991(Bhupathiraju et al, , 1993(Bhupathiraju et al, , 1994a. It is easier to understand such variability when strains of the same species are isolated from geographically distinct environments, as with the subspecies of H. saccharolyticum (Cayol et al, 1994;Zhilina et al, 1992).…”
Section: Cellular Fatty Acid Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 -12 However, different anaerobic halophilic organisms have been isolated so far. For example, Haloanaerobacter chitinovorans, which was isolated from a saltern in California; 13 Haloanaerobium congolense from an African oil field; 14 Halanaerobium lacusrosei from sediment of a hypersaline lake; 15 Haloanaerobium praevalens 16 and Haloanaerobium alcaliphilum 17 from Great Salt Lake sediment. These organisms were also identified in canned food.…”
Section: Introductionmentioning
confidence: 99%